CSIG-20. L3MBTL3 SUPPRESSES MEDULLOBLASTOMA TUMORIGENESIS THROUGH MODULATION OF THE NOTCH/RBPJ SIGNALING PATHWAY. (9th November 2020) - Zhang, Honglai; Xu, Tao; Peabody, Claire; Fernández, Ester Calvo; Budhathoki, Rashmi; Huang, Philip Chi-En; Hughes, Elizabeth D; Saunders, Thomas L; Kuick, Rork; Magnuson, Brian; Camelo-Piragua, Sandra; Rual, Jean-François
Abstract: The NOTCH/RBPJ pathway governs cell proliferation in many biological contexts, including SHH and Group#3 medulloblastoma (MB) tumorigenesis. Using our proteomic platform, we discovered an interaction between RBPJ, a key co-factor of NOTCH for the modulation of the NOTCH/RBPJ signaling pathway, and L3MBTL3, a methyllysine reader. L3MBTL3 is recruited by RBPJ on chromatin at the enhancers of NOTCH/RBPJ target genes to repress their expression. Deletions of the L3MBTL3 locus are observed in patients with WNT and Group#3 MB and expression of L3MBTL3 in the SHH MB-derived cell DAOY inhibits cell growth, suggesting a putative tumor suppressor role for L3MBTL3 in MB. To further investigate the putative role of L3MBTL3 as a suppressor of MB tumorigenesis, we used our novel L3mbtl3 KO mouse in combination with a genetically engineered ND2:SmoA1 mouse model of SHH MB in a survival analysis. Furthermore, to identify the biological processes regulated by L3mbtl3 in MB, we analyzed by RNA-seq the transcriptome of L3mbtl3 KO mouse cerebella. Our survival analysis validated in vivo our hypothesis that L3mbtl3 is a tumor suppressor in this disease context. Indeed, our data show that [ ND2:SmoA1 ; L3mbtl3 +/ - ] mice have a significantly lower survival rate than ND2:SmoA1 mice ( P = 0.032; Log-rank test). Moreover, our RNA-seq studies showed that L3MBTL3 regulates cell fate in the cerebellum via modulation the NOTCH/RBPJ signaling pathway. Hence, the RBPJ-L3MBTL3 interaction is at the heart of a molecular mechanism governing the repression of NOTCH/RBPJ target genes and malfunction of this molecular mechanism contributes to L3MBTL3's tumor suppressor role in MB through aberrant "de-repression" of NOTCH/RBPJ target genes. Our discovery provides insights into the tumor suppressor role of the L3MBTL3 in MB that could be harnessed in the future for the therapeutic benefit of patients with MB.